ANALISIS FAKTOR YANG MEMPENGARUHI HUBUNGAN JANGKA PANJANG - Marlien Marlien; Tri Darmayanti (Jurnal Bisnis dan Ekonomi, 2006)
Long term relationship between a company as a buyer and a supplier is a perception of mutual dependency which is beneficial for both parties. Commitment and dependency, trustworthiness and satisfaction influnce that long term relationship. The trustworthines, however, represents a determining factor since its function is an credibility and benefalence. Credibility creates expectation toward both written and oral statements which an trustworthy and reliable expressed by both parties as working partners. Benevolence makes both parties consider and motivate each other concerning their  welfare to work together. Satisfaction, on the other hand, will arouse the willingness to trustact with another company which will help abstain the credibility in order to cooperate in the future. Keywords : commitment, dependency trustworthness, long term relationship,   credibility, benevolence, satisfaction.